National Survey of Pharmacy Practice at MOH Hospitals in Saudi Arabia 2016-2017: Pharmacy Quality Management and Drug Information Service - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Alattyh, Radi Abdullah (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia 2016- 2017: Pharmacy Quality Management and Drug Information services. Methods: It is a 4-months cross-sectional National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia. The study consisted of two parts; the demographic information and the second part contained eighty-five questions divided into nine domains drove from American Society of Health-System Pharmacists (ASHP) and Saudi Pharmaceutical Society (SPS) survey, the international standard of Joint Commission of Hospital Accreditation in addition to the local standards of Saudi Center of healthcare accreditation. The parts were pharmacy management and resources, prescribing and medication control, preparation of medications and dispensing, Computerized and pharmacy technology, clinical pharmacy services, drug monitoring and patient’s education, Pharmacy inventory control and stock management, Pharmacy education and training, and Pharmacy total quality management and drug information services. The study discussed and analyzed National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia: Pharmacy Quality Management and Drug Information services. All analysis is done through survey monkey system. Results: The survey questionnaire was distributed to 185 of hospitals, the rate of reply, was 105 (56.75%) hospitals. The average scores of pharmacies total quality management were 2.43 (48%) and the program implemented at 3.03 (48.6%). The highest services implemented in quality management was inpatient outpatient dispensing (3.45) inpatient dispensing (3.36) and medication errors preventing and monitoring (3.34). Most of hospital pharmacies had the staff job description 103 (98.10%), Policy and Procedure of Pharmacy 102 (97.14%), and Mission of the Pharmacy 102 (97.14%) and vision of pharmacy 101 (96.19%). While the tiny percentages found were pharmacy annual plan 92 (87.62%), and Patient satisfaction of pharmacy services 90 (85.71%). The highest services of Drug Information Services available at the hospitals were Medications Errors preventing and monitoring (3.53) followed by Respond to Drug Information Questions (3.5) and Participate on Pharmacy and Therapeutic Committee (3.44). Conclusion: The half of hospital pharmacies implemented pharmacy total quality management with the variable of drug information services activities. Targeting of education and training on quality management and drug information is required. Also, the incremental human resources of both services are highly recommended to improve pharmacy services offers to the patients at Ministry of Health hospital in Kingdom of Saudi Arabia.
Keywords: Pharmacy quality management; Drug information services; Ministry of health; Saudi arabia